Trial of Acute Femoral Fracture Fixation (TrAFFix): study protocol for a randomized controlled feasibility trial - Griffin, X; Costa, M; Achten, J; Dritsaki, M; Baird, J; Parsons, N (BioMed Central, 2017)
Background Distal femur fractures are a source of considerable morbidity and best treatment is currently uncertain. The Trial of Acute Femoral Fracture Fixation (TrAFFix) is a randomised, parallel group feasibility study designed to inform the design of a later definite clinical trial comparing intramedullary nails and locking plates for the treatment of distal femur fractures. Methods/Design Patients aged 50 years and older with a femoral fracture within the distal two Müller squares are potentially eligible for inclusion. Participants are randomly allocated to receive fixation with either an intramedullary nail or distal locking plate. Measurements (EuroQol 5 Dimensions, Dementia quality of life, Disability Rating Index) are collected at baseline, six weeks and four months. The recruitment rate will be assessed across seven participating centres over a total of fifty-two centre-months which is expected after ten months of recruitment. Objectives are - feasibility phase, to assess recruitment rate and completion rate of the primary outcome measure; process evaluation, to assess the generalisability and likely success of a future trial; definitive trial, quantify and draw inferences on observed differences in health-related quality of life at 4 months between the study intervention groups (nail versus plate). A favourable opinion was granted by the Wales Research Ethics Committee (16/WA/0225), study-wide NHS approval was given by the Health Research Authority (IRAS 206745), and participating NHS trusts provided local approvals. This study was funded by the National Institute for Health Research Health Technology Assessment (HTA 15/59/22).